Contorted polycyclic aromatic hydrocarbon: promising Li insertion organic anode. Issue 26 (18th June 2018) - Park, Jaehyun; Lee, Cheol Woo; Joo, Se Hun; Park, Ju Hyun; Hwang, Chihyun; Song, Hyun-Kon; Park, Young Seok; Kwak, Sang Kyu; Ahn, Seokhoon; Kang, Seok Ju
Abstract : Contorted hexabenzocoronene molecule as a promising Li insertion organic anode. Abstract : Enhancing the performance of carbon-based anode materials in Li-ion battery (LIB) systems is of considerable interest in terms of next-generation LIB host electrodes, because the unique reversible intercalation–de-intercalation process of such materials ultimately facilitates increases in LIB performance and longevity. This study explored the potential of a new class of carbon-based contorted hexabenzocoronene (c-HBC) as an anode material for high-performance LIB systems. The exploitation of the polymorphic crystalline nature of c-HBC resulted in successful development of a LIB anode based on a newly found crystal phase of trigonal R 3̄ by solvent and subsequent thermal annealing. Our in-depth analysis based on cross-sectional transmission electron microscopy, grazing incidence X-ray diffraction, and computational investigation revealed further advantages of using contorted molecules in LIB systems. For instance, the resulting electrochemical characteristics using half-cell architecture clearly reflected single-stage Li insertion behavior associated with the large interspacing and short diffusion length of c-HBC molecule during the discharging process. In addition, the battery exhibited excellent rate capability and cycle endurance, highlighting the suitability of c-HBC as an anode material for high-performance LIBs.